Research in the Atlantic Sector of the Southern Ocean and Propagation of Antarctic Bottom Water in the Atlantic - Eugene Morozov (Water, 2023)
This article belongs to the Special Issue “Physical and Biological Properties of Waters in the Region of the Antarctic Peninsula and Adjacent Basins of the South Atlantic,”: a Special Issue that is dedicated to recent research in the Atlantic sector of the Southern Ocean and Antarctica Peninsula region [.]